(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The main cause of failure of multi-storey multi-bay reinforced concrete frames during seismic motion is the soft storey sway mechanism or column sway mechanism. If the frame is designed on the basis of strong column-weak beam concept the possibilities of collapse due to sway mechanisms can be completely eliminated. In multi storey frame this can be achieved by allowing the plastic hinges to form, in predetermined sequences only at the ends of all the beams while the columns remain essentially in elastic stage and by avoiding shear mode of failures in columns and beams. This procedure for design is known as Capacity Based Design (CBD) which would be safer than current design philosophy used for earthquake resistant design of multi storey multi bay reinforced concrete frames in India. The present Dissertation work is an effort to understand Capacity Based Design Approach. In this Work a three storey workshop building a linear static analysis is carried out and then building is designed by force based method. Then for Capacity Based Design columns are designed for magnified moment by moment magnification factor. A mechanism is applied to subsequent failure of storey before vertical members by strengthening the columns with respect of beams. Apart from improving axial strength of columns, shear capacity of beams and columns also improved in capacity based method. Reinforcement obtained from this design compared to Force Based Design and concluded that CBD method is little conservative but it ensure to prevent column sway mechanism.